A prospective randomized controlled trial of bone metabolism in patients with charcot foot - Ekaterina L. Zaitseva; Alla Y. Tokmakova; Viktor M. Zhilyaev; Natalia M. Malysheva; Natalia I. Sazonova; Gagik R. Galstyan; Aleksandr V. Vorontsov (Сахарный диабет)
BACKGROUND: Diabetic neuroosteoarthropathy (DNOAP, Charcot’s foot) - is a progressive destructive inflammatory disease of the osteoarticular apparatus of the foot, untimely and inadequate treatment of which can lead to the formation of gross deformities. More often, DNOAP is unilateral, bilateral lesion is relatively rare. It is not always possible to trace the relationship between the debut of DNOAP with trauma and chronic hyperglycemia. There is data demonstrating the role of individual pro-inflammatory factors in the pathogenesis of DNOAP, however, studies combining the evaluation of various metabolic markers of Charcot’s foot formation are currently extremely poor. AIM: To evaluate the hormonal and metabolic markers of bone formation and resorption in patients with DNOAP and without this diabetic complication. METHODS: A prospective, controlled trial included 70 patients with type 2 diabetes mellitus (37 men and 43 women) who formed 2 groups: group 1 included patients with DNOAP, group 2 was formed by patients with diabetes without foot skeleton damage. All patients underwent a study of 1,25-OH-vitamin D, sclerostin, pro-MMP-1, C-terminal propeptide type 1 collagen (PICP), type 1 collagen, osteocalcin, PTH, 25-OH-vitamin D, beta-cross-slaps. RESULTS: The results of the studies confirmed the presence of vitamin D deficiency in all patients with diabetes mellitus included in the study, revealed the absence of statistically significant differences between the groups in the values of sclerostin, pro-MMP-1; 25-OH-vitamin D, type I collagen, and osteocalcin (p > 0.05). However, significant differences were found in the 1.25-OH vitamin D levels: patients with DNOAP presented the lower rates of 1,25-OH-vitamin D in comparison to control group (p <0.05). Beta-cross and PICP levels were significantly higher in DNOAP patients as well (p <0.05). Those findings show the more severe collagen degradation in patients with DNOAP and can be the genetically predisposed cause of DNOAP development. Though further studies are needed. CONCLUSION: In patients with DNOAP a decrease in 1,25-OH-vitamin D levels was found, as well as the alteration of the synthesis and destruction of collagen (beta-cross-slaps and PICP) compared to patients with diabetes mellitus without osteoarticular disorders.